PENINGKATAN KEMAMPUAN KOMUNIKASI SISWA MELALUI CONTENT BASED INSTRUCTION BERBANTUAN ROLE PLAYING PADA MATA PELAJARAN IPAS KELAS V UPT SPF SD GALANGAN KAPAL 1 KOTA MAKASSAR - Nurdin, Putriyana; Suryani Sahabuddin, Erma; Faisal, Muhammad (STKIP Subang, 2026)
This research aimed to improve students’ communication skills through the implementation of the Content-Based Instruction (CBI) approach assisted by the Role Playing technique in IPAS learning for fifth-grade students at UPT SPF SD Galangan Kapal 1, Makassar. The background of this study was the low level of students’ communication skills during IPAS learning, which was indicated by students’ lack of confidence in speaking, asking questions, and expressing ideas clearly. The learning process was still teacher-centered, causing limited student participation in classroom activities. This study employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The research subjects were fifth-grade students. Data were collected through observation of teacher and student activities, assessment of students’ communication skills, and IPAS learning achievement tests. The data were analyzed descriptively by examining percentages and average scores obtained in each cycle. The results showed that the implementation of the Content Based Iinstruction approach assisted by the Role Playing technique gradually improved students’ communication skills. In Cycle I, students’ communication skills were still categorized as fair to low. However, after improvements were made in Cycle II, a significant increase was observed. Students became more confident in speaking, more active in asking questions, better at expressing ideas, and more engaged in group discussions. In addition, students’ IPAS learning outcomes also improved, with most students achieving good achievement categories. Based on these findings, it can be concluded that the Content-Based Instruction approach assisted by the Role Playing technique is effective in improving students’ communication skills in IPAS learning at the elementary school level.